Engaging the Disengaged : inclusive approaches to teaching the least advantaged - McKenna, Tarquam, 1954-; Cacciattolo, Marcelle; Vicars, Mark; Steinberg, Shirley R., 1952- (Cambridge University Press, 2013)
Engaging the Disengaged addresses strategies and models of immersive teaching and learning that lead to successful schooling outcomes. The new Australian Curriculum emphasises the importance of improved educational participation. This book will equip pre-service teachers with the tools and strategies they need to successfully implement these priorities. Drawing together a diverse range of experts, this book offers innovative ways of thinking about student engagement. Addressing education across early primary, middle and secondary school levels, it explores how differences in culture, sexuality and wealth can alienate students, and examines challenges faced by schools in rural, remote and high-poverty settings. It also offers new ideas for engaging students in subjects such as mathematics, physical education and the arts. Contemporary, real-life case studies help connect theory to practice. Each chapter also includes learning objectives, further reading suggestions and a reflective closure, as well as a set of strategies for invigorating disadvantaged students.